Creative Destruction and Subjective Well-Being - Aghion, Philippe; Akcigit, Ufuk; Deaton, Angus; Roulet, Alexandra (American Economic Review, 2016)
In this paper we analyze the relationship between turnover-driven growth and subjective well-being. Our model of innovation-led growth and unemployment predicts that: (i) the effect of creative destruction on expected individual welfare should be unambiguously positive if we control for unemployment, less so if we do not; (ii) job creation has a positive and job destruction has a negative impact on well-being; (iii) job destruction has a less negative impact in areas with more generous unemployment insurance policies; and (iv) job creation has a more positive effect on individuals that are more forward-looking. The empirical analysis using cross-sectional MSA (metropolitan statistical area)-level and individual-level data provide empirical support to these predictions. (JEL I31, J63, J65, O33, O38)